2010
DOI: 10.1099/vir.0.025817-0
|View full text |Cite
|
Sign up to set email alerts
|

An RGG sequence in the replication-associated protein (Rep) of Tomato yellow leaf curl Sardinia virus is involved in transcriptional repression and severely impacts resistance in Rep-expressing plants

Abstract: Truncated versions of the replication-associated protein (Rep) of Tomato yellow leaf curl Sardinia virus (TYLCSV) can interfere with various viral functions and the N-terminal 130 aa are sufficient for strongly inhibiting C1-gene transcription and virus replication and confer resistance in transgenic plants. In this work, we analysed the relevance of an RGG sequence at aa 124-126, highly conserved in begomoviruses, in these inhibitory functions as well as in the subcellular localization of Rep. Although no rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In a previous study, we showed that Rep 130 , when ectopically expressed in N. benthamiana plants, retains some of the biochemical and biological functions described for the full‐length Rep. In particular, Rep 130 was shown to tightly repress TYLCSV C1 gene transcription (Lucioli et al ., ) and to be specifically targeted to the nucleus (Sardo et al ., ), both functions being essential for its ability to inhibit TYLCSV replication in single cells and whole plants (Lucioli et al ., ; Sardo et al ., ). In addition, the ability of TYLCSV Rep 130 to inhibit TYLCSV replication, but not that of the Portuguese strain of Tomato yellow leaf curl virus TYLCV‐Mld (AF105975) (Lucioli et al ., ), suggests that either Rep 130 is inactive in recognizing and cutting the conserved nonanucleotide sequence of geminiviruses or that this activity is not able to confer TYLCV‐Mld resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that Rep 130 , when ectopically expressed in N. benthamiana plants, retains some of the biochemical and biological functions described for the full‐length Rep. In particular, Rep 130 was shown to tightly repress TYLCSV C1 gene transcription (Lucioli et al ., ) and to be specifically targeted to the nucleus (Sardo et al ., ), both functions being essential for its ability to inhibit TYLCSV replication in single cells and whole plants (Lucioli et al ., ; Sardo et al ., ). In addition, the ability of TYLCSV Rep 130 to inhibit TYLCSV replication, but not that of the Portuguese strain of Tomato yellow leaf curl virus TYLCV‐Mld (AF105975) (Lucioli et al ., ), suggests that either Rep 130 is inactive in recognizing and cutting the conserved nonanucleotide sequence of geminiviruses or that this activity is not able to confer TYLCV‐Mld resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of TYLCSV, plant-expressed Rep130 retains the ability to be compartmentalized within the nucleus/nucleolus and to inhibit C1 gene transcription, whereas a further deletion of 10 amino acids from its C-terminus abolishes both functions (Lucioli et al, 2003;Sardo et al, 2011). In addition, a recent deletion analysis conducted on the Rep of Tomato golden mosaic virus (TGMV), a bipartite begomovirus, has shown that the Rep region responsible for the binding to the small ubiquitin-related modifier (SUMO)-conjugating enzyme (SCE1) lies inside this N-terminal domain between amino acids 85 and 114 (Sánchez-Durán et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the expression of the Rep protein of tomato yellow leaf curl Sardinia virus (TYLCSV) lacking a C-terminal end resulted in TYLCSV resistance in tomato ( Brunetti et al., 1997 ). Sardo et al. (2011) have used a C-terminal-truncated Rep transgene to develop TYLCSV resistance in N .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the AC2 ORF brings about the suppression of plant defence responses and the expression of late viral genes in the later phase of geminiviral infection. Apart from this in Tomato yellow leaf curl Sardinia virus (TYLCSV) Rep protein contains a highly conserved RGG sequence at amino acids located at 124-126 positons which when mutated alters the subcellular localization and inhibits its transcriptional autoregulation [66].…”
Section: Rep As Transcription Regulatormentioning
confidence: 99%